Preparation of corrosion inhibitor loaded zeolites and corrosion resistance of carbon steel in simulated concrete pore solution. (20th November 2019) - Yang, Heng; Li, Weihua; Liu, Xiaoyan; Liu, Ang; Hang, Peng; Ding, Rui; Li, Tianyu; Zhang, Yumei; Wang, Wei; Xiong, Chuansheng
Highlights: A new inhibitor loaded zeolite was developed for the protection of carbon steel. DIA-ZEO prolongs the long-term corrosion protection of inhibitor. DIA-ZEO reduces the amount of inhibitor compared with pure DIA. DIA-ZEO promotes the film formation quality of the inhibitor on steel. Abstract: Corrosion inhibitor loaded zeolites (inhibitor-loaded ZEO) were prepared and developed for corrosion inhibition of carbon steel in simulated concrete pore solution containing 3.5%NaCl (Cl-SCPS). SEM, EDS, and FTIR were applied to characterize the inhibitor-loaded ZEO. Elemental analysis (EA) and total organic carbon (TOC) methods were used to analyze the inhibitor loading and releasing processes in zeolite. OCP, EIS and polarization tests were carried out. After 336 h, the OCP of DIA-ZEO was higher than that of pure DIA. EIS fitting results show the corrosion inhibition efficiency of DIA-ZEO is about 2% higher than that of pure DIA after 336 h. The results of polarization test are basically consistent with those of EIS, which indicates that DIA-ZEO prolong the long-term effectiveness of DIA. Furthermore, DIA-ZEO reduces the amount of inhibitor added by nearly 30% compared with pure DIA. This may be due to the controlled release of inhibitors by zeolite boosting the formation of denser protective film on the surface of carbon steel.